No association found between CYP2D6 genotype and early breast cancer events in tamoxifen-treated patients. (February 2014) - Markkula, Andrea; Hjertberg, Maria; Rose, Carsten; Ingvar, Christian; Jernström, Helena
Abstract Background. CYP2D6 is considered the key enzyme in tamoxifen metabolism. Several studies have investigated the relationship between the CYP2D6 genotype and tamoxifen treatment outcome, with discrepant results. CYP2D6 inhibitor use, aromatase inhibitor use, and chemotherapy may account for some of the discrepancies. We examined the association between CYP2D6 genotype and early breast cancer events in tamoxifen-treated breast cancer patients, in relation to CYP2D6 inhibitor use, aromatase inhibitor use, and chemotherapy. Material and methods. Pre- and postoperative questionnaires on lifestyle and concomitant medications were completed by 634 primary breast cancer patients between 2002 and 2008, among whom 333 patients had ER-positive tumors and received tamoxifen. CYP2D6*3, *4, *6, *10 and *41 were genotyped. Information on clinical data, breast cancer events, and tumor characteristics was obtained from patients' charts, population registries, the Regional Tumor Registry, and pathology reports. Results. Median follow-up was 4.9 years. Neither poor metabolizers (adjusted HR 0.50; 95% CI 0.07–3.82) nor intermediate metabolizers (adjusted HR 1.00; 95% CI 0.47–2.11) had an increased risk of early breast cancer events when compared with extensive metabolizers. CYP2D6 activity score (taking into account genotype and CYP2D6 inhibitor use) was not associated with early breast cancer events (LogRank, Ptrend = 0.44). Conclusions. CYP2D6 genotype was not associated with tamoxifen treatment outcome, even when CYP2D6 inhibitor use, aromatase inhibitor use, or chemotherapy was taken into account. CYP2D6 genotype may be of minor importance for tamoxifen-treated patients in Scandinavia.